European Union issue voting in East and West Europe: The role of political context - Tillman, Erik; de Vries, Catherine (Springer Nature, 2011)
Recent research has shown the rise of domestic contention over European integration. This paper examines the extent to which preferences over European integration influence domestic party support in 19 European Union (EU) member states in West and East-Central Europe (ECE). The analysis finds broad evidence of EU issue voting across the countries included in the analysis, but the effect of the EU issue on party preferences is stronger in ECE. These results are consistent with the view that the same underlying causal dynamics explain party and voter behavior in both West and ECE, but the post-communist legacy shapes the political and economic contexts in the ECE states, resulting in predictable differences between the two regions.
Keywords: Comparative Politics; EU Politics; European Politics; European Union Politics; Party Research; European Economic Integration